Viscosity, Miscibility Studies and Mechanical Properties of Pullulan/Poly(vinyl alcohol) Blends at 30 ºC and 40 ºC - Jayaprakash, M.S.; Shivakumar, K; Shashidhar; Vishnuvardhan, T.K. (Asian Journal of Chemistry, 2019)
The miscibility studies of pullulan and poly(vinyl alcohol) (PVA) blends by reduced viscosity measurements, refractometry, mechanical properties and SEM analysis. Viscometric measurements at 30 and 40 ºC were taken using Ubbelohde viscometer. Ultrasonic interferometric was used to measure the ultrasonic velocities of different blend compositions. Refractive indices of blend solutions with different compositions were measured directly with an Abbe′s refractometer with thermostat containing water circulated at 30 and 40 ºC. The mechanical properties, refractive index, ultrasonic velocity and density studies showed that there is an increase of all these with PVA content in the blends. But SEM studies have given an indication of immiscibility in the blend system. Overall, pullulan/PVA blends have shown good physical and mechanical properties particularly for 90/10 composition.